Loan Loss Provisioning Behavior in Chinese Banking - Jiang, Bi-Fei (2016)
Using a panel database of 31 Chinese banks during 2010-2014, we investigate the loan loss provisioning (LLP) behavior and the determinants that may exert an effect on provisions. We test the hypothesis of income smoothing, capital management and the business cycle, also with the impact of cost efficiency on banks’ provisioning behavior. Our empirical results do not support the income smoothing and capital management hypothesis. However, we find a mixed result in the cyclical effect which is that the procyclical effect plays a dominant role while there’s also countercyclical practice in the banking industry. The evidence of cost efficiency also supports the procyclicality.